Analisis Penilaian Akuntabilitas Pengelolaan Zakat Dalam Perspektif Islam Pada Badan Amil Zakat Nasional (BAZNAS) Kota Baubau - Syah Putra, Muhammad Adriyan; Sujana, I Wayan (Journal of Culture Accounting and Auditing, 2024)
This research aims to find out how to analyze the accountability assessment of zakat management from an Islamic perspective at the Baubau City National Zakat Amil Agency (BAZNAS). The type of research used in the research used in this research is qualitative research. The data analysis method used in this research is a qualitative descriptive analysis method, using observation, interviews, documentation and literature study data collection methods. Based on the research results, accountability for zakat management from an Islamic perspective at BAZNAS Baubau City is appropriate based on the accountability trilogy. However, there are three indicators where one indicator is appropriate, namely accountability to Allah with the concept of trust and the other two indicators are not appropriate, namely the indicator of accountability to humans with PSAK 109 and accountability to nature with the Green Office concept.